2011
DOI: 10.1111/j.1749-6632.2010.05870.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and cellular mechanisms of cancer prevention

Abstract: The use of novel and improved chemopreventive and chemotherapeutic agents for the prevention and treatment of cancer is on the rise. Natural products have always afforded a rich source of such agents. Epidemiological evidence suggests that a higher flavonoid intake is associated with low cancer risk. Accumulating data clearly indicate that the induction of apoptosis is an important component in the chemoprevention of cancer by naturally occurring dietary agents. Resveratrol, a naturally occurring polyphenol, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
166
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(174 citation statements)
references
References 49 publications
3
166
0
1
Order By: Relevance
“…Resveratrol has shown much promise in treating cancer in laboratory animals and in vitro human cell studies [68][69][70], yet there is still a large void in human research. This may soon change, as six of the clinical trials currently listed for resveratrol on www.clinicaltrials.gov (Table 2 in Supporting Information) include cancer patients as a target population.…”
Section: Current Limitations To Human Clinical Trial Datamentioning
confidence: 99%
“…Resveratrol has shown much promise in treating cancer in laboratory animals and in vitro human cell studies [68][69][70], yet there is still a large void in human research. This may soon change, as six of the clinical trials currently listed for resveratrol on www.clinicaltrials.gov (Table 2 in Supporting Information) include cancer patients as a target population.…”
Section: Current Limitations To Human Clinical Trial Datamentioning
confidence: 99%
“…Cell proliferation and DNA synthesis is decreased through its inhibitory actions on ribonucleotide reductase, DNA polymerase, and ornithine decarboxylase activities as well as by cell cycle arrest at the G2-S checkpoint. Apoptosis is induced in various malignant cells by resveratrol through up-regulation of CD95L expression, caspase activation, stabilization of p53, and inhibition of nuclear factor κB activity (Athar et al, 2009;Delmas et al, 2011;Shukla and Singh, 2011). Several pathways are intertwined and influence additional mechanisms involved in cellular invasion and metastasis, such as the regulation of growth factors and matrix metalloproteins (Weng & Yen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One well-known example of the stilbenes is resveratrol, and its antitumor activity has been intensively studied. Several in vivo and in vitro studies have shown that resveratrol inhibits the growth of cancer cells and effects various molecular targets associated with cancer progression such as the Wnt signaling pathway, nuclear factor-kappa B (NF-κB), and the MAPK/ERK pathway in different types of cancer (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…One well-known example of the stilbenes is resveratrol, and its antitumor activity has been intensively studied. Several in vivo and in vitro studies have shown that resveratrol inhibits the growth of cancer cells and effects various molecular targets associated with cancer progression such as the Wnt signaling pathway, nuclear factor-kappa B (NF-κB), and the MAPK/ERK pathway in different types of cancer (17,18).Previously, two novel stilbenes, cis-and trans-suffruticosol D, were extracted from the seeds of Paeonia (5). The two chemicals have similar structures as the mass fragmentation pattern of trans-suffruticosol D was very similar to cis-suffruticosol D, with cis-suffruticosol D varying only from trans-suffruticosol D in its olefinic hydrogen signal (Fig.…”
mentioning
confidence: 99%